High-pressure studies of macrocycle coordination complexes - Tidey, Jeremiah P. (2016)
Chapter 1: An introduction is given to high-pressure crystallography with the experimental design and equipment required outlined. The basic theory that underpins X-ray diffraction and structure solution is covered with emphasis given to points that raise considerations for high-pressure crystallographic studies; key software and their uses are briefly introduced. A literature survey of molecular coordination complexes under pressure is given that provides a detailed view of the typical phenomena observed and interrogated in such work. Chapter 2: Recrystallisation of [PdCl2([9]aneS2O)] ([9]aneS2O = 1-oxa-4,7-dithiacyclononane), 1, and [PtCl2([9]aneS2O)], 2, by diffusion of Et2O vapour into solutions of these complexes in CH3NO2 has yielded three phases of 1 and two phases of 2. The phase of 1, herein designated α-1, was obtained under ambient conditions. A second phase, designated β-1, was initially also obtained by this method; following the advent of a third phase, γ-1, all subsequent efforts over a period of a year to crystallise β-1 yielded either γ-1, which was typically obtained by carrying out the recrystallisation at elevated temperature, or α-1, commonly found throughout the study. This persistent absence of a phase which could initially be crystallised with ease led to the conclusion that β-1 was an example of a ‘disappearing polymorph’. The first phase obtained of 2, designated α-2, was obtained by recrystallisation under ambient conditions and is isomorphous and isostructural with α-1. The second phase, β-2, was obtained by slight elevation of the recrystallisation temperature and was found to be isomorphous and isostructural with β-1. Subsequently, β-2 was used to seed the growth of the disappearing polymorph β-1. No third phase of 2 ("γ-2") has been isolated. Density functional theory calculations were employed to aid in rationalising this behaviour. Chapter 3: The three reported phases of the mononuclear macrocyclic Pd(II) complex [PdCl2([9]aneS2O)] (1) were each studied up to pressures exceeding 90 kbar using high pressure single crystal X-ray diffraction. The α and γ phases both exhibited smooth compression of the unit cell parameters with third-order Birch-Murnaghan bulk moduli of 14.4(8) and 7.6(6) GPa, respectively. Between 68.1 and 68.7 kbar β-1 was found to undergo a reversible transformation to a phase denoted β’ and characterised by a tripling of the unit cell volume. Across the phase transition, rearrangement of the conformation of the bound macrocycle at two of the resulting three unique sites gave rise to an extensively disordered structure. This phenomenon was largely owed to a close and approximately linear C−H···H−C approach between macrocycles. Density functional theory calculations were employed to further understand the high-pressure behaviour of the phases. Cooling from 290 to 90 K in complementary variable temperature crystallographic studies revealed similar effects as ca. 5 kbar pressure. Chapter 4: The two reported phases of the mononuclear macrocyclic Pt(II) complex [PtCl2([9]aneS2O)] (2) were each studied up to pressures exceeding 90 kbar using high pressure single crystal X-ray diffraction. The α phase exhibited smooth compression of the unit cell parameters with third-order Birch-Murnaghan bulk modulus of 11.8(5) GPa. Between 65.2 and 69.9 kbar β-2 was found to undergo an incomplete rearrangement of the macrocycle that was not characterised by a phase transition as seen for the corresponding Pd(II) phase. The β phase was also indicated to be more resistant to compression than the α phase with a third-order Birch-Murnaghan bulk modulus of 13.5(5) GPa. The conformational rearrangement was again rationalised by a close and approximately linear C−H···H−C approach between macrocycles. Density functional theory calculations were employed to further understand the high-pressure behaviour of these two phases and why β-1 and β-2 might differ. Cooling from 290 to 90 K in complementary variable temperature crystallographic studies again revealed similar effects as ca. 5 kbar pressure. Chapter 5: The previously unreported solvate [Pd([9]aneS3)2](PF6)2·2CH3NO2 is studied using high-pressure crystallography, high-pressure solid-state UV/vis spectroscopy and density function theory calculations to interrogate the piezochromism previously observed by this group. Up to 49.3 kbar, gradual sky blue to dull green piezochromism was observed with considerable compression of the elongated axial Pd···S interactions. A reversible P21/c → P-1 phase transition with doubling of the unit cell volume was observed between 49.3 and 51.0 kbar. This was accompanied by a dull green to orange stepwise piezochromism and characterised by an organised reorientation of the coordination axes in 50 % of the cations. The phase transition had a range of effects on the axial interactions which remained compressible in the high-pressure phase. No further piezochromism was clearly observed. Density functional theory calculations showed a fair match with experimentally obtained spectra and strongly indicated that the piezochromism is primarily owed to compression of the axial interaction. These calculations also indicated that outer-sphere effects further modulate the piezochromism, but gave no evidence for a cause of the phase transition. The phase transition was thus rationalised as a response to the large value of the PV term of the Gibb’s free energy associated with the transition. The ambient pressure structures of two other previously unreported solvates are also reported. Chapter 6: The templated polyiodide framework [Ag([18]aneS6)]I7 were studied to ca. 45 kbar. Each of the two crystals employed in this study underwent two phase transitions: at ca. 11 kbar an R-3m → R3m transition was observed in both crystals. This appeared to be ferroelectric in nature and was associated with a change in bonding of the polyiodide network from 3∞[I−·(I2)6/2] to 3∞[I7−]. Analysis of the calculated Mayer bond orders for the catenating I−···I2 interactions supported this description of the bonding. Compression of the first phase appears essentially the same for both crystals; compression through the second phase differed between crystals and the second phase transition, at ca. 40 kbar in both cases, resulted in differing monoclinic phases. The second transition was associated with the ordering of the conformation of the macrocycle: one phase appeared ordered from the perspective of the refinement and the macrocycle adopted the previously unseen [84114] conformation by Dale analysis. The other phase appears disordered from the perspective of the refinement but would appear to comprise alternating enantiomers of the [333333] conformer. The differing conformation of the macrocycle in the third phase was taken as indicative of differing major components in the disordered lower phases. This point of difference in turn rationalised the different response to pressure in the second phase: compression of the second phase is limited by interactions between cations while the first phase is dependent on the catenating I−···I2 interactions which are identical between crystals. Chapter 7: A summary of the key findings of this body of work is given along with suggested avenues for future studies. This thesis closes with the wider reaching considerations that are highlighted by this body of work.